Binge Ethanol-Induced HDAC3 Down-Regulates Cpt1α Expression Leading to Hepatic Steatosis and Injury - Kirpich, Irina (2013)
BACKGROUND: Recently, we have demonstrated that acute alcohol exposure due to binge drinking leads to hepatic steatosis with the deregulation of hepatic histone deacetylase (HDAC) expression. Various class I, II, and IV HDACs were down-regulated, whereas expression of HDAC3 was solely up-regulated. Hence, in the present work, we specifically examined the mechanistic role of HDAC3 in the development of hepatic steatosis occurring in response to binge alcohol administration. METHODS: C57BL/6 mice were gavaged 3 times with ethanol (EtOH) at a dose of 4.5 g/kg. HDAC inhibitor, Trichostatin A (TSA) was simultaneously injected intraperitoneally at a dose of 1 mg/kg. Hepatic steatosis, injury, expression of HDAC3 and carnitine palmitoyltransferase 1α (CPT1α) were evaluated. HDAC3 and histone H3 acetylation levels at the Cpt1α promoter were analyzed by chromatin immunoprecipitation (ChIP). RESULTS: The binge EtOH-mediated increase in HDAC3 was prevented by simultaneous administration of HDAC inhibitor, TSA, which markedly attenuated hepatic steatosis and injury. Importantly, HDAC3 inhibition was able to normalize the down-regulation of Cpt1α expression. Causal role of HDAC3 in the transcriptional repression of Cpt1α was demonstrated by increased HDAC3 binding at the thyroid receptor element site in the Cpt1α distal promoter region. Further, a resultant decrease in the transcriptionally permissive histone H3 lysine 9 acetylation in the proximal promoter region near the transcriptional start site was observed. Notably, TSA treatment reduced HDAC3 binding and increased H3K9 acetylation at Cpt1α promoter leading to increased Cpt1α expression. These molecular events resulted in attenuation of binge alcohol-induced hepatic steatosis. CONCLUSIONS: These findings provide insights into potential epigenetic mechanisms underlying transcriptional regulation of Cpt1α in the hepatic steatosis occurring in response to binge EtOH administration.